Physiological and anthropometric determinants of sport climbing performance - Mermier, C. M.; Janot, J. M.; Parker, D. L.; Swan, J. G. (British Journal of Sports Medicine, 2000)
Objective: To identify the physiologicaland anthropometric determinants of sport climbing performance. Methods: Forty four climbers (24 men, 20 women) of various skill levels (self reported rating 5.6-5.13c on the Yosemite decimal scale) and years of experience (0.10-44years) served as subjects.They climbed two routes on separate days to assess climbing performance. The routes (11 and 30 m in distance) were set on two artificial climbing walls and were designed to become progressively more difficult from start to finish. Performance was scored according to the system used in sport climbing competitions where each successive hand-hold increases by one in point value. Results from each route were combined for a total climbing performance score. Measured variables for each subject included anthropometric (height, weight, leg length, arm span, % body fat), demographic (self reported climbing rating, years of climbing experience, weekly hours of training), and physiological (knee and shoulder extension, knee flexion, grip, and finger pincer strength, bent arm hang, grip endurance, hip and shoulder flexibility, and upper and lower body anaerobic power).These variables were combined into components using a principal components analysis procedure. These components were then used in a simultaneous multiple regression procedure to determine which components best explain the variance in sport rock climbing performance. Results: The principal components analysis procedure extracted three components. These were labelled training, anthropometric, and flexibility on the basis of the measured variables that were the most influential in forming each component. The results of the multiple regression procedure indicated that the training component uniquely explained 58.9% of the total variance in climbing performance.The anthropometric and flexibility components explained 0.3% and 1.8% of the total variance in climbing performance respectively. Conclusions: The variance in climbing performance can be explained by a component consisting of trainable variables. More importantly, the findings do not support the belief that a climber must necessarily possess specific anthropometric characteristics to excel in sport rock climbing.